A second species of cotopaxia (umbelliferae/ apiaceae), from colombia (1984)
Cotopaxia whitei (Umbelliferae/ Apiaceae) , a new species from the Sierra Nevada de Santa Marta, Dpto. Magdalena, Colombia, is here described andillustrated. The other known species of Cotopaxia, C. asplundii, is found only in the mountains of Ecuador.